Dataset of mRNA levels for dopaminergic receptors, adrenoceptors and tyrosine hydroxylase in lymphocytes from subjects with clinically isolated syndromes - Cosentino, Marco (Data Brief, 2016)
This data article presents a dataset of mRNA levels for dopaminergic receptors, adrenoceptors and for tyrosine hydoxylase, the rate-limiting enzyme in the synthesis of catecholamines, in peripheral blood mononuclear cells as well as in CD4+ T effector and regulatory cells from subjects with clinically isolated syndromes (CIS), which is a first episode of neurological disturbance(s) suggestive of multiple sclerosis. CIS subjects are divided into two groups according to their eventual progression, after 12 months from CIS, to clinically established multiple sclerosis. The data reported are related to the article entitled "Dopaminergic receptors and adrenoceptors in circulating lymphocytes as putative biomarkers for the early onset and progression of multiple sclerosis" (M. Cosentino, M. Zaffaroni, M. Legnaro, R. Bombelli, L. Schembri, D. Baroncini, A. Bianchi, R. Clerici, M. Guidotti, P. Banfi, G. Bono, F. Marino, 2016) [1].